The predicament of Turkish modern identity: The east-west oscillation in Snow - Brameswari, Catharina; Iskarna, Tatang (Universitas Pendidikan Indonesia, 2021)
This research uses Orhan Pamuk’s Snow in order to reveal the tension and oscillation between the East and the West which is represented by Ataturk’s forced modernization on the restriction of veils in schools and public places. Pamuk uses Kars, a small city in Turkey’s border which always coved by snow, to describe this tension. The women are presented as the oppressed who silently end their life as their way to protect their beliefs and tradition as well as the weapon to fight against the oppressor. To dismantle Pamuk’s work that highlights the endless oscillation, I employ the method of library research by presenting the internal struggle experienced by the main characters that are forced to embrace Western tradition. This research deals with two issues namely oscillation and complex desire to imitate the Others experienced by the main characters the as well as the solutions to the predicament that are offered by Pamuk in Snow. This research is also accompanied by Said’s Orientalism and Bhabha’s Postcolonialism that are employed to illuminate the solutions. Additionally, the information on Turkey’s history and socio-politic condition are presented. This research is a way to show how the oscillation can be solved by embracing one culture without leaving the other. Additionally, it is also a tool to raise the readers’ awareness towards the problem on the predicament of the East and West and develop their critical thinking towards the forced modernity by the oppressor.